1973
DOI: 10.1203/00006450-197311000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Cyst(e)ine and Methionine across the Human Placenta

Abstract: ExtractAfter intravenous loads in pregnant women, L-methionine, L-leucine, and L-ornithine were transferred from maternal to fetal plasma against a two-to threefold difference in initial concentration. Cyst(e)ine is unique among the free amino acids of plasma in that its basal concentration in maternal plasma was equal to or greater than that in fetal plasma. Furthermore, after intravenous loads with L-cystine or L-cysteine, total cyst(e)ine (cystine and cysteine) was transferred less readily to the fetal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…In contrast, most other amino acids are present in higher concentrations in fetal plasma than in maternal plasma [5][6][7], The mechanism by which cyst(e)ine transfer across the placenta is limited is not known. In order to gain further insight into the factors that might limit cyst(e)ine transfer across the placenta, we first confirmed the original ob servation of Gaull et al [4], Second, we con firmed that the placenta does concentrate cyst(e)ine. Third, we used a rat model to eval uate the effects of excess cysteine on mater nal-fetal cyst(e)ine transfer and to estimate the capacity of maternal rats and their respec tive fetuses to metabolize excess cyst(e)ine over a short period of time.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…In contrast, most other amino acids are present in higher concentrations in fetal plasma than in maternal plasma [5][6][7], The mechanism by which cyst(e)ine transfer across the placenta is limited is not known. In order to gain further insight into the factors that might limit cyst(e)ine transfer across the placenta, we first confirmed the original ob servation of Gaull et al [4], Second, we con firmed that the placenta does concentrate cyst(e)ine. Third, we used a rat model to eval uate the effects of excess cysteine on mater nal-fetal cyst(e)ine transfer and to estimate the capacity of maternal rats and their respec tive fetuses to metabolize excess cyst(e)ine over a short period of time.…”
supporting
confidence: 58%
“…Gaullet al [4] observed that cysteine injected into human mothers at the time of voluntary pregnancy termination was not taken up in significant amounts by fetal organs. These authors suggested that the rapid uptake of cyst(e)ine by fetal tissues was, therefore, not the cause of the reported low fetal plasma cyst(e)ine concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other amino acids, the concentration of cysteine is lower in the fetal than the maternal circulation (28). Despite the low fetal plasma concentration of cysteine, high metallothionein concentrations corresponding to the hepatic zinc concentrations imply that adequate substrate is available for metallothionein synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it also serves as a precursor of glutathione, a major cellular antioxidant, as well as CoA, taurine, and inorganic sulfur. Several tissues in the body are capable of cysteine synthesis (14), which is why cysteine is considered nutritionally dispensable. However, increasing evidence that oxidant stress is linked to many disease pathologies and aging has focused attention on the antioxidant functions of cysteine and its product, glutathione, leading some to suggest that cysteine is a conditionally indispensable dietary nutrient (15)(16)(17).…”
mentioning
confidence: 99%